2022
DOI: 10.1111/bju.15748
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of prostatic urethral lift vs prostatic artery embolization for benign prostatic hyperplasia: a systematic review and network meta‐analysis

Abstract: Objective To assess and compare the clinical efficacy and safety of prostatic urethral lift (PUL) and prostatic artery embolization (PAE) for the treatment of lower urinary tract symptoms (LUTS) in patients with benign prostatic hyperplasia (BPH) by means of a systematic review and network meta‐analysis. Methods A systematic literature search was performed using PubMed and Web of Science from inception to March 2021 to identify randomized controlled trials (RCTs) that compared PUL or PAE with either transureth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…PUL using the UroLift® System (Teleflex, Inc., Wayne, PA, USA) is one of the MISTs for BPH, which provides short operative time and rapid relief of LUTS compared with the conventional treatments 1,2 . Several meta‐analyses have reported that PUL has fewer serious adverse events and was superior in preserving sexual function than conventional surgeries and showed similar retreatment rates than other MISTs 3,4 . The most frequently reported complications of PUL are spontaneously resolving dysuria and hematuria; however, the occurrence of major complications, such as pelvic hematoma, has rarely been reported 5–10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PUL using the UroLift® System (Teleflex, Inc., Wayne, PA, USA) is one of the MISTs for BPH, which provides short operative time and rapid relief of LUTS compared with the conventional treatments 1,2 . Several meta‐analyses have reported that PUL has fewer serious adverse events and was superior in preserving sexual function than conventional surgeries and showed similar retreatment rates than other MISTs 3,4 . The most frequently reported complications of PUL are spontaneously resolving dysuria and hematuria; however, the occurrence of major complications, such as pelvic hematoma, has rarely been reported 5–10 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Several meta‐analyses have reported that PUL has fewer serious adverse events and was superior in preserving sexual function than conventional surgeries and showed similar retreatment rates than other MISTs. 3 , 4 The most frequently reported complications of PUL are spontaneously resolving dysuria and hematuria; however, the occurrence of major complications, such as pelvic hematoma, has rarely been reported. 5 , 6 , 7 , 8 , 9 , 10 We describe two Japanese cases of pelvic hematoma after PUL.…”
Section: Introductionmentioning
confidence: 99%